Geração de Sinais de RF por Mistura de Harmônicas de Portadoras Ópticas Moduladas em Amplificadores Ópticos Semicondutores10.14209/jcis.2001.4 - C. Bordonalli, A.; L. Benitez, J.; A. Guimarães, J.; M. Gallep, C.; Conforti, E. (Journal of Communication and Information Systems, 2015)
The gain-crossed property of semiconductor optical amplifiers is experimentally investigated. It was observed that optically feed-backed saturated amplifiers could achieve similar performance as that of cascaded amplifiers, offering up to 10 dB gain to two 8-nm-appart modulated optical carriers. Due to saturation. the amplifier gain mechanism is altered. leading to a mixing effect that causes the frequency components of the optical signals to be exchanged. For optical carriers modulated at 250 and 100 MHz. this mixing effect produced, after photodetection, up and down-converted electronic components at 150 and 650 MHz, respectively.